Глобальные решения и инвариантные торы дифференциально-разностных уравнений - Белан, Е.П. (Український математичний журнал, 1997)
Доведено існування m-параметричної сім'ї глобальних розв'язків системи диференціально-різницевих рівнянь. Для диференціально-різницевих рівнянь на горі введено число обертання. Розглянуто задачу про збурення інваріантного тора системи диференціально-різницевих рівнянь. Досліджено задачу про періодичні та квазіперіодичні розв'язки диференціально-різницевого рівняння другого порядку. We prove the existence of an m-parameter family of global solutions of a system of difference-differential equations. For difference-differential equations on a torus, we introduce the notion of rotation number. We also consider the problem of perturbation of an invariant torus of a system of difference-differential equations and study the problem of the existence of periodic and quasiperiodic solutions of second-order difference-differential equations.